COVID-19 infection recurrence presenting with meningoencephalitis (2020)
Coronavirus disease 2019 (COVID-19) infection can involve many organs, such as central nervous system, including in relapse. We describe the case of a 64-year-old woman with microbiologically confirmed COVID-19–induced respiratory distress whose treatment resulted in a negative nasopharyngeal swab reverse transcriptase PCR (RT-PCR) result for COVID-19. However, after a few weeks, relapse occurred, as indicated by symptoms of acute meningoencephalitis. Results of COVID-19 RT-PCR testing from her cerebrospinal fluid, nasopharyngeal and tracheal aspiration specimens became positive again, but COVID-19 serum antibodies were negative. We therefore note that symptoms with neurologic involvement can be one of COVID19’s first presentations, or they can appear at relapse. Regular evaluation of patients during convalescence is therefore necessary.